PENERAPAN MODEL PEMBELAJARAN PAKEM DALAM MENINGKATKAN HASIL BELAJAR PADA MATERI SEPAK BOLA SISWA KELAS IVB SD NEGERI 013 MEKARSARI - Aslinda, Aslinda (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
This study aims to describe learning outcomes through the application of PAKEM learning model. The subjects of the study were the students of grade IVb SD Negeri 013 Mekarsari. Improvement of learning outcomes in terms of four categories, namely the ability to absorb, the effectiveness of learning, mastery of student learning both mastery of individual and classical completeness and mastery of learning outcomes. Instruments used for data collection are oral tests and written tests in the form of LKS conducted after the learning process. The results showed that the percentage of student completeness increased from 19.40% to 55.40% categorized well, the effectiveness of learning is categorized very effective with an average of 88.46%. While the completeness of student learning outcomes expressed. Based on the results of the study, it can be concluded that the application of PAKEM learning model can improve learning outcomes on the material of the students of class IV B grade SD Negeri 013 Mekarsari.